A Qualitative Study on Identity Construction among Teachers Working with Students with Disabilities - Rostami, Farzad; Yousefi, Mohammad Hosein; Amini, Davoud (International Journal of Multicultural Education, 2021)
The purpose of this study was to explore multiple facets of the professional identities of Iranian in-service teachers in exceptional schools. The study adopted a qualitative design. The data were collected through in-depth interviews with 14 in-service teachers. The participants were selected through purposeful sampling. Each interview lasted up to 40 minutes. The whole procedure of the data collection was audio-recorded, and verbatim transcriptions were made. Thematic analysis was utilized to analyze the qualitative data. Three themes emerged: relationships, lower identity, and professional identity. The study has some implications for policymakers, curriculum designers, educational psychology, and teacher educators.